2008
DOI: 10.1177/0269216307087147
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of hyperprolactinaemia as an entity in psychiatric patients

Abstract: This paper explores chronologically the evolution of raised prolactin levels as an entity in psychiatric patients. Menstrual problems were described in patients with schizophrenia prior to the introduction of antipsychotic medication, but galactorrhoea and gynaecomastia were not commonly seen until the advent of antipsychotics. Following the introduction of antipsychotic medication single case reports of patients with galactorrhoea and gynaecomastia appeared. These were followed by a collection of case reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Hyperprolactinemia can affect sexual and reproductive functions in both genders, and the clinical presentation generally depends on the magnitude of prolactin elevation (Serri, Chik, Ur, & Ezzat, 2003). Additionally, chronic hyperprolactinemia has been linked to an increased risk of osteoporosis and probably breast cancer (Kohen & Wildgust, 2008;Misra, Papakostas, & Klibanski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperprolactinemia can affect sexual and reproductive functions in both genders, and the clinical presentation generally depends on the magnitude of prolactin elevation (Serri, Chik, Ur, & Ezzat, 2003). Additionally, chronic hyperprolactinemia has been linked to an increased risk of osteoporosis and probably breast cancer (Kohen & Wildgust, 2008;Misra, Papakostas, & Klibanski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The first generation antipsychotics (FGA) bind to dopamine D 2 receptors on the pituitary lactotroph cells, thereby inhibiting the action of hypothalamic dopamine, leading to hyperprolactinaemia. Although this and its accompanying sexual dysfunction have been recognized for many years, hyperprolactinaemia has largely been ignored because of the former lack of alternative psychiatric treatments 1 …”
Section: Introductionmentioning
confidence: 99%
“…2008a); this is however more of a concern in regard to first‐generation antipsychotics, and risperidone and amisulpride. Hyperprolactinaemia is one of the most common disorders of the hypothalamic‐pituitary axis (Kohen & Wildgust 2008). Since the mid‐1970s it was established that the prescription of antipsychotic medication within therapeutic doses can cause hyperprolactinaemia (Beaumont et al.…”
Section: Antipsychotic Medicationmentioning
confidence: 99%
“…This case was borne out in a recent study where hyperprolactinaemia was found in 38% of asymptomatic outpatients (Bushe & Shaw 2007). There are prolactin receptor sites throughout the human body, yet its full function at each of these is not yet fully established (Wieck & Haddad 2003, Kohen & Wildgust 2008). One concerning side effect of hyperprolactinaemia that is gaining more attention is breast cancer.…”
Section: What Are the Consequences Of Hyperprolactinaemia?mentioning
confidence: 99%